2013
DOI: 10.1080/10549811.2013.791231
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Control and Nursery-Plantation Genotypic Correlations for Growth Characteristics of White Spruce Somatic Clones

Abstract: Height and diameter of white spruce clones were measured over two growing seasons in a forest nursery and for 4 more yr at two field sites. Clonal heritability (H c 2 ) was moderate and stable in the nursery, but decreased with age, reaching 0.26 and 0.11 for height and 0.14 and 0.04 for diameter, respectively, at the two field sites. Height exhibited weak to moderate H c 2 and strong genotypic correlations with the different growth characteristics. The strong age-age genotypic correlations (≥0.809) and nurser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
1
6
0
2
Order By: Relevance
“…The lower height growth at the warmest site (Watford) may be interpreted as an existing maladaptation of tested seed sources to warming conditions in southern Québec (Rainville et al, 2014 ). Considering previous findings showing a strong age-age-genetic correlation of height growth in white spruce (Li et al, 1993 ; Wahid et al, 2013 ), one may believe that this observed parabolic growth pattern could be stable over the next years during the juvenile stage. Longer-term data are however required to confirm this pattern, although a similar pattern was observed with older white spruce seed sources on different sites (Andalo et al, 2005 ).…”
Section: Discussionmentioning
confidence: 55%
“…The lower height growth at the warmest site (Watford) may be interpreted as an existing maladaptation of tested seed sources to warming conditions in southern Québec (Rainville et al, 2014 ). Considering previous findings showing a strong age-age-genetic correlation of height growth in white spruce (Li et al, 1993 ; Wahid et al, 2013 ), one may believe that this observed parabolic growth pattern could be stable over the next years during the juvenile stage. Longer-term data are however required to confirm this pattern, although a similar pattern was observed with older white spruce seed sources on different sites (Andalo et al, 2005 ).…”
Section: Discussionmentioning
confidence: 55%
“…The assessment of seedlings height during the establishment phase on forest sites indicated the presence of a significant variation among seed sources. Height growth, like hardening and bud set, is a trait that usually shows moderate, but significant, heritability ( h 2 F = 0.17 to 0.45) in white spruce families, for instance under nursery growth conditions and when measured 8 year-old trees on forest planting sites ( Li et al, 1993 ; see also Cornelius, 1994 ; Wahid et al, 2013 ). Heritability for height was stronger for clones measured during their first 2 years of growth in a nursery ( H 2 C = 0.60) ( Wahid et al, 2012b , 2013 ) and after four years of clonal tests ( H 2 C = 0.26) ( Wahid et al, 2012b ), as well as for white spruce rooted cuttings from 75 families at the end of their first ( h 2 F = 0.76) and second ( h 2 F = 079) growing seasons ( Gravel-Grenier et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, 98% of the seeds used to produce white spruce seedlings were from improved sources (first- and second-generation seed orchards) that exhibited a genetic gain of 10 to 15% in height compared to unimproved plantation stock ( Rainville et al, 2003 ; Beaulieu et al, 2009 ). The production of multiple clones by somatic embryogenesis is currently integrated into the operational chain for rooted cuttings and processes for their characterization and selection have been developed both in nurseries ( Lamhamedi et al, 2000 ; Wahid et al, 2012a ) and on reforestation sites ( Grossnickle, 2000 ; Lamhamedi and Gravel-Grenier, 2012 ; Wahid et al, 2012b , 2013 ). Association genetics and genomic selection approaches have also been developed for different traits related to growth and wood quality of this species ( Beaulieu et al, 2011 , 2014a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…(Lamhamedi et al, 2000Wahid et al, 2012a), en bouturage , en site de plantation (croissance, degré de branchaison, nutrition minérale, etc.) (Beaulieu et Bernier-Cardou, 2006 ;Wahid et al, 2012b) et en fonction de la stabilité de leur performance en pépinière et en site de plantation Wahid et al, 2013). L' utilisation de pieds mères somatiques produisant un plus grand nombre de branches longues (plus de boutures par pied mère) aurait pour conséquence d'augmenter la fréquence de leur géno-type dans les plantations et pourrait réduire leur valeur à long terme dans le cas de plantations destinées à la filière sciage parce qu'ils produiraient du bois avec plus de noeuds par comparaison aux pieds mères somatiques moins branchus ; la qualité des sciages varie en effet en fonction de la grosseur et du diamètre des noeuds (Bowyer et al, 2005).…”
Section: Analyses Statistiquesunclassified
“…En effet, l'intégration de l'ES dans la filière de bouturage de l'Épinette blanche fait suite à nos travaux qui englobent notamment l'optimisation des techniques d'acclimatation sans recourir à la brumisation pour améliorer de façon significative le taux de survie (> 95 %) des clones somatiques de l'Épinette blanche lors de leur transfert en sol (Lamhamedi et al, 2003), l'évaluation de la variabilité clonale, de la qualité morphophysiologique et de la performance des clones de l'Épinette blanche en pépinière (Lamhamedi et al, 2000 ;Wahid et al, 2012a) et en plantation (Rainville et al, 2011 ;Wahid et al, 2012b). D'autres travaux ont mis l'accent sur la détermination des paramètres génétiques, de la stabilité de la performance des clones et des corrélations génotypiques âge-âge « pépinière-plantation » (Wahid et al, 2013), ainsi que sur l'évaluation de la qualité des semences produites par des clones somatiques (Colas et Lamhamedi, 2010, 2014. Certains travaux ont également porté sur l'utilisation des clones somatiques de l'Épinette de Norvège (Picea abies Karst.)…”
unclassified